2017
DOI: 10.1002/ejic.201601415
|View full text |Cite
|
Sign up to set email alerts
|

Organoaluminium Complexes Derived from Anilines or Schiff Bases for the Ring‐Opening Polymerization of ε‐Caprolactone, δ‐Valerolactone and rac‐Lactide

Abstract: Reaction of R 1 R 2 CHN=CH(3,5-tBu 2 C 6 H 2 -OH-2) (R 1 = R 2 = Me L 1 H; R 1 = Me, R 2 = Ph L 2 H; R 1 = R 2 = Ph L 3 H) with slightly greater than one equivalent of R 3 3 Al (R 3 = Me, Et) afforded the complexes [(L 1-3 )AlR 3 2 ] (L 1 , R 3 = Me 1, R 3 = Et 2; L 2 , R 3 = Me 3, R 3 = Et 4; L 3 R 3 = Me 5, R 3 = Et 6); complex 1 has been previously reported. Use of the N,O-ligand derived from 2,2′-diphenylglycine afforded either 5 or the byproduct [Ph 2 NCH 2 (3,5-tBu 2 C 6 H 2 -O-2)AlMe 2 ] (7). The known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 96 publications
0
14
1
Order By: Relevance
“…Over the past 2 decades, our group have been contributing to the development of the field. Simple arylimino compound 188 ( Figure 34) proved inactive in the ROP of ε-CL [109], while the 2,4-t Bu-salicylaldehyde derivatives 189-196 exhibited interesting activity towards the polymerization of different monomers [110]. In the presence of BnOH as co-activator, complexes 189 and 195 were the most performing catalysts in the ROP of ε-CL, leading to complete monomer conversion at 80 • C within 3 and 1 h for the former and the latter, respectively.…”
Section: Aluminummentioning
confidence: 99%
“…Over the past 2 decades, our group have been contributing to the development of the field. Simple arylimino compound 188 ( Figure 34) proved inactive in the ROP of ε-CL [109], while the 2,4-t Bu-salicylaldehyde derivatives 189-196 exhibited interesting activity towards the polymerization of different monomers [110]. In the presence of BnOH as co-activator, complexes 189 and 195 were the most performing catalysts in the ROP of ε-CL, leading to complete monomer conversion at 80 • C within 3 and 1 h for the former and the latter, respectively.…”
Section: Aluminummentioning
confidence: 99%
“…The catalysts and initiators used for the ROP of CL are discussed below. Organo aluminium complexes derived from anilines were used for the ROP of CL . In 2018, Jiang et al reported a novel catalyst for the ROP of CL .…”
Section: Introductionmentioning
confidence: 99%
“…Organo aluminium complexes derived from anilines were used for the ROP of CL. 1 In 2018, Jiang et al reported a novel catalyst for the ROP of CL. 2 Galia and co-workers 3 studied the ROP of CL using wet β-cyclodextrin as a novel catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature a few papers published on these metals complexes as catalysts toward polymerization of lactide, lactone or ethylene [3][4][5][6]. The use of Schiff base ligation has received more interest because of easy to prepare [7] and versatile applications of Schiff base and their complexes as biological activity, antifungal properties, anticancer properties, application in modern technologies, application in synthesis and chemical analysis [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%